2017
DOI: 10.18632/oncotarget.15092
|View full text |Cite
|
Sign up to set email alerts
|

Statins in conditions other than hypocholesterolemic effects for chronic subdural hematoma therapy, old drug, new tricks?

Abstract: Chronic subdural hematoma (CSDH) is one of the most common intracranial hematomas worldwide with a high incidence in the general population. However, the optimum treatment for CSDH is Burr-hole drainage with or without rinse Considering the poor outcomes of CSDH in aged patients, and ambiguous prediction of recurrence in many sides of recurrent CSDHs who have been analyzed, new effective therapies are needed for those CSDHs who are predicated to have poor prognosis for surgery and/or have a higher risk of recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Mechanisms of statins that are discussed as potentially promoting pleiotropic effects in CSDH include the inhibition of inflammation, promotion of blood vessel formation and maturation, an elevation of the number of endothelial precursor cells, and the suppression of vascular endothelial growth factor [27]. Preclinical studies suggest a biphasic effect of statins, whereby the aforementioned responses only occur with lower concentrations, while higher statin doses lead to an inhibition both of angiogenesis and of the growth and migration of endothelial precursor cells [21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of statins that are discussed as potentially promoting pleiotropic effects in CSDH include the inhibition of inflammation, promotion of blood vessel formation and maturation, an elevation of the number of endothelial precursor cells, and the suppression of vascular endothelial growth factor [27]. Preclinical studies suggest a biphasic effect of statins, whereby the aforementioned responses only occur with lower concentrations, while higher statin doses lead to an inhibition both of angiogenesis and of the growth and migration of endothelial precursor cells [21,23].…”
Section: Discussionmentioning
confidence: 99%
“… 12 13 A recent trial of dexamethasone showed fewer recurrent cases, but less favorable outcomes and more adverse events. 14 Studies of atorvastatin use in rodents 15 16 and humans 17 18 19 20 21 found that it led to a reduction in CSDH volume without the requirement for surgery and showed no adverse effects. While all of these studies showed the efficacy of atorvastatin in reducing the need for surgical treatment, they did not show its efficacy in preventing recurrence in surgical cases.…”
Section: Introductionmentioning
confidence: 99%
“…As a means of reducing recurrent cases, further therapeutic strategies have been developed. These range from pharmacological agents such as dexamethasone and tranexamic acid to MMA embolization as a way to stop angiogenesis [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%